Hydatid cyst of liver: different modalities of management and outcome - Gattu, E. Muniswamy; Chopada, Mehul (International Surgery Journal, 2016)
Background:Echinococcosis affects the liver rather than other organs in 50-70 % of cases. While surgery is recognized as the only satisfactory method of treatment for liver echinococcosis (LE), many controversial results have been reported but total excision of the cyst alone or with part of the liver appear to be the most effective. This method is not always feasible, since it depends on the size and site of the cyst. Methods: The study information was collected using pre-tested semi structured questionnaire. The questionnaire was presented in the Department for critical review, following which necessary changes were made in the questionnaire. For all patients meticulous records was maintained regarding clinical features, family history, dietary habits and by performing various investigations. Results:Surgery was the mainstay of management. Out of 30 patients, 24 patients underwent complete pericystectomy (80%), 4 patients underwent incomplete pericystectomy (13.4%) and 3 patients had other procedures along with pericystectomy. Only 2 patients managed conservatively (6.7%). Conclusions:A variety of techniques, both radical and conservative, are used in the treatment of liver hydatid cyst.